A non-noble metal catalyst Cu / TiO2-P25, its preparation method, and its application in the synthesis of N,N-dimethyl-p-toluidine in a heterogeneous system.
Patent Information
- Application Number
- CN202411241762.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-09-05
AI Technical Summary
[0029] 1) The Cu/TiO2-P25 prepared by the deposition-precipitation method of this invention uses non-precious metals as the active phase and P25 type TiO2 as the support, which greatly reduces the cost of raw materials and is green and environmentally friendly.
Smart Images

Figure CN119386864B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal catalysts, specifically relating to a non-noble metal catalyst Cu / TiO2-P25, its preparation method, and its application in the synthesis of N,N-dimethyl-p-toluidine in a heterogeneous system. Background Technology
[0002] N,N-Dimethyl-p-toluidine, with the molecular formula C9H 13 N,N-dimethyl-p-toluidine (N-dimethyl-p-toluidine) is a pale yellow liquid with a relative molecular weight of 135.21, a melting point of -25°C, and a boiling point of 211°C. It is soluble in organic solvents such as water, ethanol, and chloroform. In organic synthesis, N-dimethyl-p-toluidine is commonly used as a catalyst, reducing agent, and intermediate. It can also be used to prepare dyes, pigments, and photosensitive materials. In the medical field, N-dimethyl-p-toluidine exhibits certain biological activity and can be used as a raw material for the synthesis of antibacterial agents and antitumor drugs. Besides these applications, N-dimethyl-p-toluidine is also widely used in organic electronics, serving as a component of organic semiconductor materials for the manufacture of organic thin-film transistors, organic light-emitting diodes, organic solar cells, and other devices. In conclusion, N-dimethyl-p-toluidine is an important organic compound with broad application and research value.
[0003] N,N-Dimethyl-p-toluidine is typically synthesized by the N-methylation of N-methyl-p-toluidine. For example, Lin et al. successfully prepared a Pd-ZnO / TiO2 catalyst by dispersing PdZn alloy particles on the surface of TiO2 using a deposition-precipitation method. They then applied this catalyst to the N-methylation reaction of N-methyl-p-toluidine with CO2 and H2, achieving a yield of 90.8% for N,N-dimethyl-p-toluidine. Kon et al. synthesized N,N-dimethyl-p-toluidine by combining Pt and MoO2... x Pt-MoO was prepared by co-loading on TiO2 x In the N-methylation reaction using TiO2 catalyst with N-methyl-p-toluidine as the substrate, the yield of N,N-dimethyl-p-toluidine reached 85%, indicating that Pt-MoO2 catalyst... x Re / TiO2 catalysts exhibit good catalytic performance. Toyao et al. synthesized a Re / TiO2 catalyst using an impregnation method, achieving a 92% yield of N,N-dimethyl-p-toluidine in the reaction of N-methyl-p-toluidine without additives. Dong prepared a low-cost heterogeneous CuAl2O3 catalyst via in-situ topological transformation, applying it to the catalytic synthesis of N,N-dimethyl-p-toluidine from p-nitrotoluene. This catalyst also exhibited strong stability and could be easily separated for continuous reuse. While these synthetic routes involve high raw material costs, the synthesis of N,N-dimethyl-p-toluidine from N-methylaniline and formaldehyde is a low-cost option with promising application prospects. Summary of the Invention
[0004] To address the aforementioned problems in the existing catalytic synthesis of N,N-dimethyl-p-toluidine, the present invention aims to provide a non-noble metal catalyst Cu / TiO2-P25, its preparation method, and its application in the synthesis of N,N-dimethyl-p-toluidine in a heterogeneous system. This preparation method is simple, has low production costs, and shows promising industrialization potential.
[0005] To achieve the above objectives, the present invention adopts the following technical solution.
[0006] One of the objectives of this invention is to provide a highly active catalyst Cu / TiO2-P25, wherein Cu is supported on P25 type TiO2, and the loading amount of Cu is 2-10 wt% of the catalyst.
[0007] Preferably, the Cu loading is 6 wt% of the catalyst.
[0008] In the Cu / TiO2-P25 catalyst, the Cu loading is expressed as a mass percentage, which will be abbreviated as 2-10% in the following text. Its meaning in this text is the same as that of 2-10 wt%.
[0009] Another object of the present invention is to provide a method for preparing the highly active catalyst Cu / TiO2-P25, the specific steps of which are as follows:
[0010] (1) Add P25 type TiO2 and copper nitrate trihydrate to pure water and stir evenly. Place the resulting suspension in a constant temperature water bath and stir vigorously. Add precipitant-Na2CO3 solution dropwise to adjust the pH to alkaline. Continue stirring the resulting mixture for 2 hours and let it stand for 30 minutes to form a precipitate.
[0011] (2) Collect the precipitate, wash it until the pH value is 7, and then put it into a vacuum drying oven at 60℃ for 12h to obtain unreduced Cu / TiO2-P25;
[0012] (3) The unreduced catalyst Cu / TiO2-P25 was placed in a tube furnace and heated and reduced in a hydrogen atmosphere. It was then naturally cooled to room temperature to obtain Cu / TiO2-P25.
[0013] Preferably, the copper salt used in step (1) is one of copper nitrate trihydrate, copper sulfate, or copper chloride.
[0014] In this preferred embodiment, since both are divalent copper salts, the technical effects are the same.
[0015] Preferably, in step (1), the molar ratio of P25 type TiO2 to copper nitrate trihydrate is 8-40:1.
[0016] Preferably, the temperature of the water bath in step (1) is 50-70℃.
[0017] Preferably, in step (1), the concentration of the Na2CO3 solution is 0.1 g / mL.
[0018] Preferably, in step (1), the pH is adjusted to 8-10 by adding the precipitant-Na2CO3 solution dropwise.
[0019] Preferably, in step (3), the heating rate of the tube furnace is 5℃ / min, the reduction temperature in the tube furnace is 200-400℃, and the reduction time is 1.5-2.5h.
[0020] Another objective of this invention is to provide the highly active catalyst Cu / TiO2-P25 for the catalytic synthesis of N,N-dimethyl-p-toluidine in a heterogeneous system, wherein the conversion of N-methylaniline reaches 100% after 8 hours of reaction, and the selectivity for N,N-dimethyl-p-toluidine is 50.8%.
[0021] The specific steps for the catalytic synthesis of N,N-dimethyl-p-toluidine using the non-noble metal catalyst Cu / TiO2-P25 of the present invention in a heterogeneous system are as follows:
[0022] (1) Select a stainless steel high-pressure reactor and insert a glass container as the reactor liner;
[0023] (2) Weigh the catalyst Cu / TiO2-P25 into the high-pressure reactor, then weigh the formaldehyde and N-methylaniline and dissolve them in n-octane solvent. After ultrasonic dispersion, place the mixture into the high-pressure reactor.
[0024] (3) After sealing the reactor, purge it three times with hydrogen gas at a pressure of 1 MPa. Maintain the hydrogen pressure at 1 MPa at room temperature and check the airtightness of the reactor.
[0025] (4) First heat the reactor to 180°C, then continue to introduce hydrogen gas to 3.5 MPa, and maintain the temperature and pressure inside the reactor for 1 hour;
[0026] (5) After the reaction is complete and cooled to room temperature, open the gas valve of the high-pressure reactor to release the gas inside the reactor until the pressure is 0, thus completing the reaction process.
[0027] After the reaction was completed, the reaction solution was filtered and injected into a gas chromatograph using a micro-injection needle. Using n-dodecane as an internal standard, the conversion rate of N-methylaniline and the selectivity of N,N-dimethyl-p-toluidine catalyzed by the catalysts in different embodiments were calculated by gas chromatography.
[0028] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0029] 1) The Cu / TiO2-P25 prepared by the deposition-precipitation method of this invention uses non-precious metals as the active phase and P25 type TiO2 as the support, which greatly reduces the cost of raw materials and is green and environmentally friendly.
[0030] 2) This invention uses formaldehyde and N-methylaniline as reaction substrates to synthesize N,N-dimethyl-p-toluidine. The method is simple, the production cost is low, and it has industrialization prospects.
[0031] 3) The 6% Cu / TiO2-P25 catalyst prepared by the method of the present invention has excellent catalytic performance; under the reaction conditions of hydrogen pressure 3.5MPa, temperature 180℃, reaction time 8h, and catalyst 50mg, the conversion rate of N-methylaniline reaches 100%, and the selectivity for N,N-dimethyl-p-toluidine is 50.8%. Attached Figure Description
[0032] Figure 1 The image shows the XRD pattern of the Cu / TiO2-P25 catalyst prepared in Example 3.
[0033] Figure 2 The image shows the time course of the Cu / TiO2-P25 catalyst prepared in Example 3.
[0034] Figure 3 The figure shows the stability performance of the Cu / TiO2-P25 catalyst prepared in Example 3.
[0035] Figure 4 This is a TEM image of the Cu / TiO2-P25 catalyst prepared in Example 3. Detailed Implementation
[0036] The technical solution of the present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0037] This invention uses Cu / TiO2-P25 prepared by loading Cu on P25 type TiO2 in different proportions as an example to test the performance and parameters of the product and determine the optimal performance of the product.
[0038] In the following specific examples 1-5, the catalysts were prepared using the following steps:
[0039] (1) Add P25 type TiO2 and copper nitrate trihydrate to pure water and stir evenly. Place the resulting suspension in a water bath at 60°C and stir vigorously. Add 0.1 g / mL Na2CO3 precipitant solution dropwise to adjust the pH to 9. Continue stirring the resulting mixture for 2 hours and let it stand for 30 minutes to form a precipitate.
[0040] (2) Collect the precipitate, wash it until the pH value is 7, and then put it into a vacuum drying oven at 60℃ for 12h to obtain unreduced Cu / TiO2-P25;
[0041] (3) The unreduced catalyst Cu / TiO2-P25 was placed in a tube furnace and heated and reduced for 2 hours in a hydrogen atmosphere. The temperature was increased to 300℃ at a heating rate of 5℃ / min and the reduction time was 2 hours. The catalyst was then naturally cooled to room temperature to obtain Cu / TiO2-P25.
[0042] In terms of raw material usage, by controlling the ratio of P25 type TiO2 to copper salt, specifically the molar ratio of copper nitrate trihydrate to 8-40:1, Cu can be loaded into the catalyst in different proportions.
[0043] The application test of the catalyst prepared by the above method in the catalytic synthesis of N,N-dimethyl-p-toluidine was carried out as follows: The reaction was conducted in a 200 mL stainless steel high-pressure reactor with a glass container inserted as a liner. 50 mg of catalyst was weighed into the high-pressure reactor, followed by 1 mmol of N-methylaniline, 2 mmol of formaldehyde, and 20 mL of n-octane. N-methylaniline and formaldehyde were dissolved in the n-octane and ultrasonically dispersed. The mixture was then placed into the high-pressure reactor. After sealing the reactor, it was purged three times with hydrogen gas (1 MPa). The hydrogen pressure was increased by 1 MPa at room temperature, and the airtightness was checked. After checking the airtightness, the magnetic rotation speed was adjusted to 550 rpm, and the reactor temperature was raised to 180 °C. Hydrogen gas was then introduced until the pressure reached 3.5 MPa, and timing began. After 1 hour of reaction, the reactor was cooled to room temperature, and the gas valve of the high-pressure reactor was opened to release the gas until the pressure reached 0 MPa.
[0044] After filtering the reaction solution, 0.4 μL was injected into the gas chromatograph using a microsyringe. The gas chromatograph used hydrogen flow rate was set to 40–60 mL / min, air flow rate to 200–300 mL / min, and carrier gas flow rate to 2–3 mL / min. The injection temperature was set to 280.0 °C, the initial column furnace temperature was set to 130 °C and held for 10 min, then increased to 220 °C at a rate of 25 °C / min and held for 10 min. The FID temperature was set to 280.0 °C. Using n-dodecane as an internal standard, the conversion rate of N-methylaniline and the selectivity of N,N-dimethyl-p-toluidine catalyzed by the catalysts in different embodiments were calculated by gas chromatography.
[0045] Example 1: Application of 2% Cu / TiO2-P25 catalytic synthesis of N,N-dimethyl-p-toluidine
[0046] The catalyst of Example 1 of this invention was tested for its application in the catalytic synthesis of N,N-dimethyl-p-toluidine. The performance test conditions and results are as follows:
[0047] Under the reaction conditions of 3.5 MPa hydrogen pressure, 180 °C temperature, 1 h reaction time, 50 mg catalyst, 2 mmol formaldehyde, and 1 mmol N-methylaniline, the catalyst conversion rate was 70.7%, and the selectivity for N,N-dimethyl-p-toluidine was 11.6%.
[0048] Example 2: Application of 4% Cu / TiO2-P25 catalytic synthesis of N,N-dimethyl-p-toluidine
[0049] The catalyst of Example 2 of this invention was tested for its application in the catalytic synthesis of N,N-dimethyl-p-toluidine. The performance test conditions and results are as follows:
[0050] Under the reaction conditions of hydrogen pressure 3.5 MPa, temperature 180 °C, reaction time 1 h, catalyst 50 mg, formaldehyde 2 mmol, and N-methylaniline 1 mmol, the catalyst conversion rate was 79.4%, and the selectivity for N,N-dimethyl-p-toluidine was 14.3%.
[0051] Example 3: Application of 6% Cu / TiO2-P25 catalytic synthesis of N,N-dimethyl-p-toluidine
[0052] The catalyst of Example 3 of this invention was tested for its application in the catalytic synthesis of N,N-dimethyl-p-toluidine. The performance test conditions and results are as follows:
[0053] Under the reaction conditions of hydrogen pressure 3.5 MPa, temperature 180 °C, reaction time 1 h, catalyst 50 mg, formaldehyde 2 mmol, and N-methylaniline 1 mmol, the catalyst conversion rate was 86.5%, and the selectivity for N,N-dimethyl-p-toluidine was 18.2%.
[0054] Example 4: Application of 8% Cu / TiO2-P25 catalytic synthesis of N,N-dimethyl-p-toluidine
[0055] The catalyst of Example 4 of this invention was tested for its application in the catalytic synthesis of N,N-dimethyl-p-toluidine. The performance test conditions and results are as follows:
[0056] Under the reaction conditions of 3.5 MPa hydrogen pressure, 180 °C temperature, 1 h reaction time, 50 mg catalyst, 2 mmol formaldehyde, and 1 mmol N-methylaniline, the catalyst conversion rate was 83.1%, and the selectivity for N,N-dimethyl-p-toluidine was 12.7%.
[0057] Example 5: Application of 10% Cu / TiO2-P25 catalytic synthesis of N,N-dimethyl-p-toluidine
[0058] The catalyst of Example 5 of this invention was tested for its application in the catalytic synthesis of N,N-dimethyl-p-toluidine. The performance test conditions and results are as follows:
[0059] Under the reaction conditions of hydrogen pressure 3.5 MPa, temperature 180 °C, reaction time 1 h, catalyst 50 mg, formaldehyde 2 mmol, and N-methylaniline 1 mmol, the catalyst conversion rate was 75.5%, and the selectivity for N,N-dimethyl-p-toluidine was 9.8%.
[0060] Application of Comparative Example 1: 6% Cu / ZnO Catalytic Synthesis of N,N-Dimethyl-p-Toluidine
[0061] The application of 6% Cu / ZnO in Comparative Example 1 for the catalytic synthesis of N,N-dimethyl-p-toluidine was tested, and the performance test conditions and results are as follows:
[0062] Under the reaction conditions of 3.5 MPa hydrogen pressure, 180 °C temperature, 1 h reaction time, 50 mg catalyst, 2 mmol formaldehyde, and 1 mmol N-methylaniline, the catalyst conversion rate was 32.4%, and the selectivity of N,N-dimethyl-p-toluidine was 1.3%.
[0063] Comparative Example 2: Application of 6% Cu / CeO2 Catalyzed Synthesis of N,N-Dimethyl-p-Toluidine
[0064] The application of 6% Cu / CeO2 in the catalytic synthesis of N,N-dimethyl-p-toluidine in Comparative Example 2 was tested, and the performance test conditions and results are as follows:
[0065] Under the reaction conditions of hydrogen pressure 3.5 MPa, temperature 180 °C, reaction time 1 h, catalyst 50 mg, formaldehyde 2 mmol, and N-methylaniline 1 mmol, the catalyst conversion rate was 25.8%, and the selectivity of N,N-dimethyl-p-toluidine was 1.7%.
[0066] Example 6: Application of 6% Cu / TiO2-P25 catalytic synthesis of N,N-dimethyl-p-toluidine
[0067] The catalyst in Example 6 of this invention was prepared by reduction at a hydrogen reduction temperature of 200°C, and then tested for its application in the catalytic synthesis of N,N-dimethyl-p-toluidine. The performance test conditions and results are as follows:
[0068] Under the reaction conditions of 3.5 MPa hydrogen pressure, 180 °C temperature, 1 h reaction time, 50 mg catalyst, 2 mmol formaldehyde, and 1 mmol N-methylaniline, the catalyst conversion rate was 82.3%, and the selectivity for N,N-dimethyl-p-toluidine was 16.7%.
[0069] Example 7: Application of 6% Cu / TiO2-P25 catalytic synthesis of N,N-dimethyl-p-toluidine
[0070] The catalyst in Example 7 of this invention was prepared by reduction at a hydrogen reduction temperature of 400°C, and then subjected to catalytic synthesis of N,N-dimethyl-p-toluidine. The performance test conditions and results are as follows:
[0071] Under the reaction conditions of hydrogen pressure 3.5 MPa, temperature 180 °C, reaction time 1 h, catalyst 50 mg, formaldehyde 2 mmol, and N-methylaniline 1 mmol, the catalyst conversion rate was 84.8%, and the selectivity for N,N-dimethyl-p-toluidine was 15.2%.
[0072] Example 8: Application of 6% Cu / TiO2-P25 catalytic synthesis of N,N-dimethyl-p-toluidine
[0073] The catalyst in Example 8 of this invention was prepared in a water bath at a temperature of 50°C, and then tested for its application in the catalytic synthesis of N,N-dimethyl-p-toluidine. The performance test conditions and results are as follows:
[0074] Under the reaction conditions of hydrogen pressure 3.5 MPa, temperature 180 °C, reaction time 1 h, catalyst 50 mg, formaldehyde 2 mmol, and N-methylaniline 1 mmol, the catalyst conversion rate was 84.9%, and the selectivity for N,N-dimethyl-p-toluidine was 16.8%.
[0075] Example 9: Application of 6% Cu / TiO2-P25 catalytic synthesis of N,N-dimethyl-p-toluidine
[0076] The catalyst in Example 9 of this invention was prepared in a water bath at 70°C, and then tested for its application in the catalytic synthesis of N,N-dimethyl-p-toluidine. The performance test conditions and results are as follows:
[0077] Under the reaction conditions of 3.5 MPa hydrogen pressure, 180 °C temperature, 1 h reaction time, 50 mg catalyst, 2 mmol formaldehyde, and 1 mmol N-methylaniline, the catalyst conversion rate was 85.6%, and the selectivity for N,N-dimethyl-p-toluidine was 17.1%.
[0078] Example 10: Application of 6% Cu / TiO2-P25 catalytic synthesis of N,N-dimethyl-p-toluidine
[0079] The catalyst in Example 10 of this invention was prepared at a solution pH of 7, and then tested for its application in the catalytic synthesis of N,N-dimethyl-p-toluidine. The performance test conditions and results are as follows:
[0080] Under the reaction conditions of hydrogen pressure 3.5 MPa, temperature 180 °C, reaction time 1 h, catalyst 50 mg, formaldehyde 2 mmol, and N-methylaniline 1 mmol, the catalyst conversion rate was 75.1%, and the selectivity for N,N-dimethyl-p-toluidine was 11.5%.
[0081] Example 11: Application of 6% Cu / TiO2-P25 catalytic synthesis of N,N-dimethyl-p-toluidine
[0082] The catalyst in Example 11 of this invention was prepared at a solution pH of 8, and then tested for its application in the catalytic synthesis of N,N-dimethyl-p-toluidine. The performance test conditions and results are as follows:
[0083] Under the reaction conditions of hydrogen pressure 3.5 MPa, temperature 180 °C, reaction time 1 h, catalyst 50 mg, formaldehyde 2 mmol, and N-methylaniline 1 mmol, the catalyst conversion rate was 83.4%, and the selectivity for N,N-dimethyl-p-toluidine was 15.8%.
[0084] Example 12: Application of 6% Cu / TiO2-P25 catalytic synthesis of N,N-dimethyl-p-toluidine
[0085] The catalyst in Example 12 of this invention was prepared at a solution pH of 10, and then tested for its application in the catalytic synthesis of N,N-dimethyl-p-toluidine. The performance test conditions and results are as follows:
[0086] Under the reaction conditions of hydrogen pressure 3.5 MPa, temperature 180 °C, reaction time 1 h, catalyst 50 mg, formaldehyde 2 mmol, and N-methylaniline 1 mmol, the catalyst conversion rate was 86.3%, and the selectivity of N,N-dimethyl-p-toluidine was 17.5%.
[0087] The catalyst prepared in Example 3 was subjected to spectral analysis, electron microscopy, catalytic activity testing, and stability testing. The test results are as follows.
[0088] Figure 1 The XRD pattern of the catalyst prepared in Example 3 is shown. Compared with JCPDS standard data, the characteristic peak of P25 is obvious, and the characteristic peak of Cu(111) crystal plane can be observed in the spectrum. The size of Cu particles in the catalyst is 12 nm.
[0089] Figure 2The figure shows the time course diagram of the catalyst prepared in Example 3. As can be seen from the figure, the conversion rates of N-methylaniline were 62.2%, 86.5%, 95.8%, 100%, 100%, and 100.0% at reaction times of 0h, 1h, 2h, 4h, 6h, and 8h, respectively, and the selectivities of N,N-dimethyl-p-toluidine were 7.8%, 18.2%, 25.4%, 37.2%, 45.6%, and 50.8%, respectively. It can be concluded that the catalyst prepared in Example 3 has high catalytic activity.
[0090] Figure 3 The figure shows the stability performance of the catalyst prepared in Example 3. As can be seen from the figure, the conversion rates of N-methylaniline were 86.5%, 87.2%, 85.1%, and 84.5% for the first, second, third, and fourth catalyst cycles, respectively, and the selectivities of N,N-dimethyl-p-toluidine were 18.2%, 17.7%, 17.4%, and 16.9%, respectively. It can be concluded that the catalyst has high stability, can be reused multiple times, and has high industrial production and application value.
[0091] Figure 4 The image shows a TEM image of the catalyst prepared in Example 3. As can be seen from the image, Cu is supported on P25 type TiO2, and the Cu particle size is 12 nm.
[0092] The catalytic performance of catalysts with different Cu loadings on aniline under the same reaction conditions is shown in Table 1.
[0093] Table 1 Effect of different Cu loading on catalytic activity
[0094]
[0095] As can be seen from Examples 1-5 in Table 1, the loading of Cu has a significant impact on the catalyst activity. When the loading content ranges from 2% to 10%, the conversion rate of N-methylaniline and the selectivity of N,N-dimethyl-p-toluidine first increase and then decrease, indicating that the catalytic performance of the catalyst also first increases and then decreases, showing a volcano-shaped trend. When the loading is 6% and the reaction time is 1 hour, the conversion rate of N-methylaniline reaches the highest level of 86.5%, and the selectivity for N,N-dimethyl-p-toluidine is 18.2%.
[0096] The catalytic performance of catalysts obtained with different supports for aniline under the same reaction conditions is shown in Table 2.
[0097] Table 2 Effect of different supports on catalyst activity
[0098]
[0099] As can be seen from Table 2 of Examples 3, 1, and 2, different types of supports have a significant impact on the activity of the catalyst. The TiO2-P25 support has a significant promoting effect on the catalytic performance of the catalyst and can significantly improve the catalytic performance of the catalyst.
[0100] The catalytic performance of catalyst products obtained at different hydrogen reduction temperatures on aniline under the same reaction conditions is shown in Table 3.
[0101] Table 3 Effect of different hydrogen reduction temperatures on catalyst activity
[0102]
[0103] As can be seen from Examples 3, 6 and 7 in Table 3, the reduction temperature of hydrogen has a great influence on the performance of the catalyst. As the reduction temperature increases from 200℃ to 400℃, the catalytic performance of the catalyst first increases and then decreases. The catalytic performance of the catalyst reaches its highest value when the reduction temperature is 300℃.
[0104] The catalytic performance of catalyst products obtained by different water bath heating temperatures on aniline under the same reaction conditions is shown in Table 4.
[0105] Table 4 Effect of different water bath heating temperatures on catalyst activity
[0106]
[0107] As can be seen from Examples 3, 8 and 9 in Table 4, the heating temperature of the water bath has a certain influence on the catalyst's activity during the catalyst preparation process, but the influence is not significant. Too high or too low a water bath temperature will weaken the activity of the prepared catalyst. The catalyst has the strongest activity when the water bath heating temperature is 60°C.
[0108] The catalytic performance of the catalyst products obtained under different solution pH conditions for aniline under the same reaction conditions is shown in Table 5.
[0109] Table 5. Effect of different solution pH values on catalyst activity.
[0110]
[0111] As can be seen from Examples 3 and 10-12 in Table 5, during the preparation of the catalyst, the pH of the solution was adjusted by the precipitant-Na2CO3 solution. The pH of the solution has a significant impact on the activity of the catalyst. If the solution is neutral, the activity of the catalyst is greatly weakened. When the solution is alkaline, the activity of the catalyst is significantly enhanced. As the alkalinity increases, the activity of the catalyst first increases and then decreases. The catalyst with the strongest activity is prepared when the pH of the solution is 9.
[0112] The above description is only a partial embodiment of the present invention and is not intended to limit the present invention. Any equivalent changes and modifications made based on the content of this invention are within the protection scope of this invention.
Claims
1. The application of a non-precious metal catalyst Cu / TiO2-P25 in the synthesis of N,N-dimethyl-p-toluidine from N-methylaniline and formaldehyde in a heterogeneous system. Under high-pressure hydrogen reaction conditions, the conversion rate of N-methylaniline reached 100% after 8 h of reaction, and the selectivity for N,N-dimethyl-p-toluidine was 50.8%. In this catalyst, Cu is supported on P25 type TiO2, and the Cu loading is 6 wt% of the catalyst. The size of the Cu particles is 12 nm.
2. The application according to claim 1, characterized in that, The preparation steps of the catalyst Cu / TiO2-P25 are as follows: (1) Add P25 type TiO2 and copper salt to pure water and stir evenly. Put the resulting suspension into a constant temperature water bath and stir vigorously. Add precipitant-Na2CO3 solution dropwise to adjust the pH to 8-10. Continue stirring the resulting mixture for 2 h and let it stand for 30 min to form a precipitate. (2) Collect the precipitate, wash it until the pH value is 7, and then dry it in a vacuum drying oven at 60 °C for 12 h to obtain unreduced Cu / TiO2-P25; (3) The unreduced catalyst Cu / TiO2-P25 was placed in a tube furnace and heated and reduced at 300°C in a hydrogen atmosphere. It was then naturally cooled to room temperature to obtain Cu / TiO2-P25.
3. The application according to claim 2, characterized in that, The copper salt used in step (1) is one of copper nitrate trihydrate, copper sulfate, or copper chloride.
4. The application according to claim 2, characterized in that, In step (1), the molar ratio of P25 type TiO2 to copper salt is 8-40:
1.
5. The application according to claim 2, characterized in that, The temperature of the water bath in step (1) is 50-70 ℃.
6. The application according to claim 2, characterized in that, In step (1), the concentration of the Na2CO3 solution is 0.1 g / mL.
7. The application according to claim 2, characterized in that, In step (1), the pH is adjusted to 9 by adding the precipitant Na2CO3 solution dropwise.
8. The application according to claim 2, characterized in that, In step (3), the heating rate of the tube furnace is 5 ℃ / min, the reduction temperature in the tube furnace is 200-400 ℃, and the reduction time is 1-3h.
Citation Information
Patent Citations
High-activity catalyst Cu-ZnO / TiO2-P25, preparation method thereof and application of high-activity catalyst Cu-ZnO / TiO2-P25 in N-methylated aniline in heterogeneous system
CN118384888A